Variabilidad espacio-temporal de aniones (SO4 -2 y Cl-) en el agua lluvia de Popayán, Colombia (2015)
This research are discussed the results of the physical and chemical variables, SO4-2, Cl-, pH and conductivity of rainwater in ten sites in the city of Popayan, Colombia. The results were determined by the technique of total deposit from September 2011 to February 2012. The objective was: to evaluate the sensitivity to acid rain formation considering possible sources of certain ions. The results were analyzed according to the spatial and temporal variability and its values were attributed to natural sources such as volcanic influence aerosols emitted from the ground and drag sea salt from the Pacific Ocean as possible sources of ions SO4-1yCl-. Results are also explained by anthropogenic inputs.